Hamilton Wedding Annoucement - unknown:::Creator::::::::::::
Adela Hermina Winckler Hamilton, wife of William John Hamilton, Steinbeck's uncle. On left of image is wedding announcement, dated 1896-03-25. The town name is listed as 'Kings City,' which was likely the transitional name from the original 'King's City.'.